Take me out of the bathtub and other silly dilly songs - Katz, Alan.; Catrow, David (New York : Margaret K. McElderry Books, 2001)
Well-known songs, including Oh, Susannah, and Row, row, row, your boat, are presented with new words and titles, such as I'm so carsick and Go, go, go to bed.
NP
Accelerated Reader AR
Keywords: Children's songs -- United States -- Texts; Humorous songs -- Texts; Humorous songs; Songs